2018
DOI: 10.1093/pcp/pcy085
|View full text |Cite
|
Sign up to set email alerts
|

A Mathematical Model of Photosynthetic Electron Transport in Response to the Light Spectrum Based on Excitation Energy Distributed to Photosystems

Abstract: To enable us to analyze more systematically the effects of the spectral distribution of light (i.e. light quality) on photosynthetic electron transport, we propose a simple mathematical model which describes electron transport reactions under light-limited conditions based on the excitation energy distributed to the photosystems. The model assumes that the rate-limiting photosystem performs the photochemical reaction at its maximum yield, while the yield in the other photosystem is passively down-regulated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…This view is based on the low action/quantum yield of photosynthesis under monochromatic far‐red light (Emerson & Lewis, ; Inada, ; McCree, ). Recent studies have revisited the Emerson enhancement effect and demonstrated the significance of the synergistic interaction between far‐red and shorter wavelengths on leaf photosynthesis (Hogewoning et al, ; Kono et al, 2020; Murakami et al, ; Zhen & van Iersel, ). It remained unclear, however, if the photosynthetic efficiency of far‐red photons at single leaf or canopy level is comparable with traditionally defined photosynthetic photons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This view is based on the low action/quantum yield of photosynthesis under monochromatic far‐red light (Emerson & Lewis, ; Inada, ; McCree, ). Recent studies have revisited the Emerson enhancement effect and demonstrated the significance of the synergistic interaction between far‐red and shorter wavelengths on leaf photosynthesis (Hogewoning et al, ; Kono et al, 2020; Murakami et al, ; Zhen & van Iersel, ). It remained unclear, however, if the photosynthetic efficiency of far‐red photons at single leaf or canopy level is comparable with traditionally defined photosynthetic photons.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a growing body of research indicates that under broad spectrum or combined lights, plants can use far‐red photons more efficiently for photosynthesis than previously thought (Hogewoning et al, ; Murakami, Matsuda, & Fujiwara, ; Zhen & van Iersel, ). Hogewoning et al () observed that the quantum yield for CO 2 fixation in cucumber measured under broad spectral light (wavelength range of 400–725 nm) is 10% to 21% higher, depending on the growth light spectra and intensity, than the weighted sum of the quantum yield determined at 19 wavelengths across the same spectral range.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that the red and green light enhancement can be described in part by the ‘enhancement effect’ or ‘Emerson effect’ which refers to the phenomenon where photosynthesis from combined spectra can be greater than the sum of its parts due to excitation energy distribution between photosystem I and photosystem II [ 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recent work demonstrates that most of the shorter wavelength photons from 400 to 680 nm over-excite photosystem II (PSII), while longer wavelength far-red photons preferentially excite photosystem I (PSI) (Evans, 1987;Hogewoning et al, 2012;Laisk et al, 2014;Zhen et al, 2018). When combining far-red with shorter wavelength photons, the balance of excitation distribution between PSII and PSI is restored, thus leading to increased leaf photochemical efficiency (Zhen and van Iersel, 2017) and photosynthetic rate (Hogewoning et al, 2012;Murakami et al, 2018). Scaling up from leaf to canopy level, Zhen and Bugbee (2020) found that far-red photons (700-750 nm) are equally efficient at driving canopy photosynthesis when added to 400 to 700 nm photons in 14 diverse crop species.…”
Section: Introductionmentioning
confidence: 99%